Costus Igneus Oro-Herbal Films: Innovative and Cost-Effective Therapy (International Journal of Food and Nutritional Sciences, 2022)
The escalating prevalence of diabetes, affecting 1 in 10 individuals across all age groups, necessitates innovative therapeutic solutions. This study introduces a novel approach to diabetes treatment through the development of oral films containing Costus Igneus extract. These films, fabricated using HPMC E5, maltodextrin, sodium alginate, PVA, propylene glycol, SSG, and honey, exhibited promising attributes. Notably, formulations F3 and F5 showcased rapid disintegration times of 11 and 12 seconds, with F3 achieving an impressive 83.57% drug release within 4 minutes. Stability assessments confirmed the reliability of formulations F3 and F4. This research underscores the potential of Costus Igneus leaf extract-based oral films to enhance bioavailability and patient adherence, offering a compelling avenue for diabetes management.